2014
DOI: 10.5194/tc-8-1275-2014
|View full text |Cite
|
Sign up to set email alerts
|

Initial results from geophysical surveys and shallow coring of the Northeast Greenland Ice Stream (NEGIS)

Abstract: Abstract. The Northeast Greenland Ice Stream (NEGIS) is the sole interior Greenlandic ice stream. Fast flow initiates near the summit dome, and the ice stream terminates approximately 1000 km downstream in three large outlet glaciers that calve into the Greenland Sea. To better understand this important system, in the summer of 2012 we drilled a 67 m firn core and conducted ground-based radio-echo sounding (RES) and active-source seismic surveys at a site approximately 150 km downstream from the onset of strea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 52 publications
8
88
3
Order By: Relevance
“…We found that the area down to 0 ∘ E/W shows a layered structure down to the lower third or quarter of the ice thickness. In this respect, Recovery Glacier is similar to the North East Greenland Ice Stream as shown in Vallelonga et al (2014). Layers within the ice are supposed to lower, once ice flows across a subglacial lake, as shown in Gudlaugsson et al (2016) and Leysinger Vieli et al (2007).…”
Section: Synthesismentioning
confidence: 91%
“…We found that the area down to 0 ∘ E/W shows a layered structure down to the lower third or quarter of the ice thickness. In this respect, Recovery Glacier is similar to the North East Greenland Ice Stream as shown in Vallelonga et al (2014). Layers within the ice are supposed to lower, once ice flows across a subglacial lake, as shown in Gudlaugsson et al (2016) and Leysinger Vieli et al (2007).…”
Section: Synthesismentioning
confidence: 91%
“…However, more recent evidence has revealed the presence of sediments beneath several areas of the GrIS (Walter et al, 2014). Christianson et al (2014) and Vallelonga et al (2014) recently identified dilatant till beneath the onset of the Northeast Greenland Ice Stream, demonstrating that the single largest ice stream in Greenland has soft basal conditions that are very similar to those observed more frequently beneath Antarctic ice streams. In west Greenland glacial sediments are widespread on the continental shelf (Dowdeswell et al, 2014;Hogan et al, 2012) and are also likely to be present subglacially.…”
Section: 1002/2017jf004297mentioning
confidence: 96%
“…By virtue of its accessibility and smaller size relative to the East and West Antarctic ice sheets, the Greenland Ice Sheet (GrIS) has been more comprehensively surveyed by ice-penetrating radar than those Antarctic ice masses. Multiple institutions have regularly collected and analyzed radar data from the GrIS since the 1960s [Gudmandsen, 1975;Jacobel and Hodge, 1995;Dahl-Jensen et al, 1997, 2003Fahnestock et al, 2001aFahnestock et al, , 2001bNixdorf and Göktas, 2001;Baldwin et al, 2003;Legarsky and Gao, 2006;Buchardt, 2009;Catania and Neumann, 2010;Bamber et al, 2013;Christianson et al, 2014;Vallelonga et al, 2014;Keisling et al, 2014]. Despite these advantages, previous efforts to directly map and interpret the radiostratigraphy of the GrIS are limited with respect to the data now available.…”
Section: Introductionmentioning
confidence: 99%